2003
DOI: 10.1364/josab.20.000037
|View full text |Cite
|
Sign up to set email alerts
|

Different regimes of low-frequency fluctuations in vertical-cavity surface-emitting lasers

Abstract: A numerical study of vertical-cavity surface-emitting lasers with optical feedback demonstrates the existence of two different types of low-frequency fluctuations (LFFs). The competition of two equally dominant polarization modes characterizes one type of LFF, while the other type is characterized by power drops in a dominant polarization mode and power bursts in the orthogonal depressed mode. We characterize and compare these two types of LFFs on the basis of their polarization properties and their dependency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition to similar feedback-induced dynamics as observed in edge-emitting semiconductor lasers, VCSEL shows extra instabilities, for example, polarization instabilities depending on the bias injection current, feedback strength, and feedback cavity length. Several experimental and theoretical studies for the dynamics in VCSELs with optical feedback have been reported up to the present [5][6][7][8][9][10][11][12][13][14][15][16]. Also the dynamics of polarization-selected optical feedback in VCSELs have been studied [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to similar feedback-induced dynamics as observed in edge-emitting semiconductor lasers, VCSEL shows extra instabilities, for example, polarization instabilities depending on the bias injection current, feedback strength, and feedback cavity length. Several experimental and theoretical studies for the dynamics in VCSELs with optical feedback have been reported up to the present [5][6][7][8][9][10][11][12][13][14][15][16]. Also the dynamics of polarization-selected optical feedback in VCSELs have been studied [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A typical example is the low-frequency fluctuation (LFF) regime where the chaotic fluctuations of the LP mode dynamics may either be in phase and then lead to similar dynamics in the VCSEL total power, or rather be anticorrelated and lead to a laser output power almost constant in time [2], [3]. Recently, we have shown that another dynamics resulting from optical feedback consists of slow hopping between the two LP modes complemented by fast anticorrelated pulses at the external cavity frequency [4]; see Fig.…”
Section: Optical Feedback: Switching and Resonancementioning
confidence: 99%
“…Furthermore, due to two linear polarization modes [18], [19], VCSELs with external-cavity optical feedback can exhibit complex dynamics. The existence of two different types of low-frequency fluctuations in VCSELs with external-cavity optical feedback was demonstrated [13]. It was also experimentally found that polarization-preserved feedback can induce random polarization mode hopping [20], [21].…”
Section: Introductionmentioning
confidence: 96%